1997
DOI: 10.1093/molehr/3.5.405
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotrophin regulation of production of tissue inhibitor of metalloproteinases-1 by luteinized human granulosa cells: a potential mechanism for luteal rescue

Abstract: Human granulosa cells were maintained in culture with extracellular matrix in the presence or absence of human chorionic gonadotrophin (HCG) using a defined culture medium. Such cultures are maintained by gonadotrophin in a manner suggesting that features of 'luteal rescue' may be occurring in vitro. Western analysis of culture medium demonstrated that the granulosa cells produced tissue inhibitor of metalloproteinases (TIMP)-1 but not TIMP-2. The presence of TIMP-1 in cultured cells was also detected immunocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…We have reported that the membrane-bound aminopeptidases expressed on ovarian cells are involved in ovarian cell function and differentiation by regulating the extracellular peptide concentrations (Fujiwara et al, 1992a,b;Nakamura et al, 1996;Tachibana et al, 1996). Recently matrix metalloproteinases and their inhibitor, named the tissue inhibitor of metalloproteinases, are also reported to regulate ovarian function as local regulators of the ovary (Hulboy et al, 1997;O'Sullivan et al, 1997). Similarly, CP-M can be proposed as a local regulator of granulosa and theca cell function, which regulates biologically active peptide concentrations by the removal of carboxy-terminal basic amino acids from these peptides.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported that the membrane-bound aminopeptidases expressed on ovarian cells are involved in ovarian cell function and differentiation by regulating the extracellular peptide concentrations (Fujiwara et al, 1992a,b;Nakamura et al, 1996;Tachibana et al, 1996). Recently matrix metalloproteinases and their inhibitor, named the tissue inhibitor of metalloproteinases, are also reported to regulate ovarian function as local regulators of the ovary (Hulboy et al, 1997;O'Sullivan et al, 1997). Similarly, CP-M can be proposed as a local regulator of granulosa and theca cell function, which regulates biologically active peptide concentrations by the removal of carboxy-terminal basic amino acids from these peptides.…”
Section: Discussionmentioning
confidence: 99%
“…It is also well established that when gonadotropins, such as LH, FSH, and hCG, added to human granulosa luteal cells in culture affect luteal function through control of apoptosis (47). The role of hCG in luteal rescue has been attributed to up-regulation of a tissue inhibitor of metalloproteinase by human granulosa luteal cells (48) or down-regulation of P 2Y receptor message in human granulosa luteal cells (49). In either case, continued presence of hCG during early pregnancy could prevent human granulosa luteal cells from entering into apoptosis, thereby possibly leading to maintenance of secretion of steroids from the rescued corpus luteum.…”
Section: F I G U R Ementioning
confidence: 99%
“…Indeed, there is some supporting evidence for this hypothesis. Induced luteolysis resulted in decreased TIMP-1 expression in the corpus luteum of non-human primates (Duncan et al, 1996a) and hCG increased TIMP-1 expression in luteinized granulosa cells in vitro (O'Sullivan et al, 1997). However, in cows, induced luteolysis increased the concentrations of TIMP-1, in contrast to the normal luteal phase, where expression tended to decrease (Smith et al, 1996).…”
Section: Tissue Inhibitors Of Metalloproteinasesmentioning
confidence: 99%